2019
DOI: 10.2166/wh.2019.303
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of human adenovirus in urban wastewater in Egypt and among children suffering from acute gastroenteritis

Abstract: Incidence of enteric viruses in sewage, the efficacy of wastewater treatment plants to remove these viruses, and health effects from their release into the surface water are very important environmental issues in the microbiology field. One of the most pathogenic enteric viruses is adenovirus which can cause a serious disease such as gastroenteritis with low grade fever and mild dehydration in humans. In this study we performed qualitative polymerase chain reaction (PCR) analysis of HAdV on 60 stool samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 39 publications
6
40
0
Order By: Relevance
“…Moreover, higher HAdV prevalence was detected at lower temperatures in autumn and winter, in agreement with previous findings [ 42 , 43 ]. However, Wang et al [ 44 ] recorded higher HAdV prevalence in summer and spring than autumn, similar to a previous study conducted in China that reported a higher prevalence in summer [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, higher HAdV prevalence was detected at lower temperatures in autumn and winter, in agreement with previous findings [ 42 , 43 ]. However, Wang et al [ 44 ] recorded higher HAdV prevalence in summer and spring than autumn, similar to a previous study conducted in China that reported a higher prevalence in summer [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…This review testifies to the extent of the problem on the African continent by reviewing over 100 investigations conducted in 13 African countries in which the occurrence (Onosi et al 2020) of enteric viruses was described in a wide range of samples including not only raw sewage but also groundwater, open water sources, bivalve shellfish and, alarmingly, drinking water. While many of these studies are limited to simple molecular detection of specific viruses in selected samples a few go further to describe the quantification, prevalence and links to disease outbreaks (see for example: El-Senousy et al 2015Elmahdy et al 2019;Okubo et al 2019).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…People suffering from viral infections can excrete 10 5 –10 13 viral particles per gram of stool. These viruses can persist in the environment for long periods, resulting in their high levels in fecal effluents 4 – 6 . The degree of wastewater contamination depends on the prevalence of viral infections and characteristics of viruses circulating in a given population 7 .…”
Section: Introductionmentioning
confidence: 99%